English Didactics in Norway 2019
DOI: 10.18261/978-82-15-03074-6-2019-16
|View full text |Cite
|
Sign up to set email alerts
|

PhD revisited: How students in Eritrea and Norway make sense ofliterature

Abstract: This chapter summarises a doctoral study (Munden, 2010) that describes, compares and explains how student teachers make sense of literature. The twenty-two participants were student teachers of English in either Norway or Eritrea. They first wrote answers to a questionnaire and then to assignments based on three literary texts. How and what they wrote provides insight into their cultural and academic expectations and socialisation, both as members of an interpretive community and as individuals. These insights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(3 reference statements)
0
2
0
1
Order By: Relevance
“…As such, it adhers to a tradition which has been richly represented in Scandinavian research on L1 and L2 literary reading (e.g. Munden, 2010;Skarstein, 2013;Smidt, 1988;Wiland, 2007Wiland, , 2013. In contrast, my concern in…”
Section: Empirical Research On Literary Reading With Relevance To Clamentioning
confidence: 89%
See 1 more Smart Citation
“…As such, it adhers to a tradition which has been richly represented in Scandinavian research on L1 and L2 literary reading (e.g. Munden, 2010;Skarstein, 2013;Smidt, 1988;Wiland, 2007Wiland, , 2013. In contrast, my concern in…”
Section: Empirical Research On Literary Reading With Relevance To Clamentioning
confidence: 89%
“…On the one hand, Article 2 presents the cultural, social and historical subject positions of literary voices, readers and texts as a point of consideration and potential explanation for diverging interpretations, noting that the competent intercultural reader takes into account how different subject positions may "make some interpretations possible/likely and others impossible/unlikely" (Hoff, 2016, p. 62). Indeed, previous empirical investigations have revealed that readers from a given culture represent a specific "interpretive community" in the sense that they draw upon distinctive discoursal positions and reading strategies (Munden, 2010). However, there are also indications that the personal and emotional dimension of the literary experience to some extent may level out such cultural differences (Wiland, 2013).…”
Section: 32) Article 2 Relies Onmentioning
confidence: 99%
“…Litt budskap, og veldig morsomt samtidig. (Mebratu,23,Eritrea) I sin doktoravhandling om norske og eritreiske studenter bekrefter Juliet Munden (Munden, 2010) indirekte Mebratus eksempel. Den sterke posisjonen muntlige fortellinger fortsatt ser ut til å ha i Eritrea kommenteres med at «… oral tradition provides both entertainment and cultural and moral instruction» (Munden, 2010, s. 172).…”
unclassified